MAKNA KATA KHASYYAH DAN KHAUF DALAM AL-QUR'AN - Dahliati Simanjuntak (Institut Agama Islam Negeri Padangsidimpuan, 2022)
An-Nazha'ir or Mutaradif is a term for different lafadz but has the same or similar meaning. On thiis occasion, the authoor will discuss thee vocabulary that is included as Mutaradif, namely lafadz khauf and Khahyah. If we see, khauf and Khashyah have the same meaning, namely fear. The qualitative method is the one used in this paper. The conclusion of this article is However, if we pay attention, the two words above have different meanings and intentions. Where the word khauf describes fear that is based on suspicion, which encourages a person to prepare steps to avoid something negative. While Khashyah is fear based on knowledge, therefore, a person will leave fear except only to Allah.